1 Answer | Add Yours
First we will rearrange the function to bring all terms to the same side:
Using the calculus method, we must take the derivative of the function and show that f'(x) is decreasing for x<-2 and that x=-2 is a root of the function for f(x)<=0 for x<=-2:
Therefore, the function is decreasing for x<-2, and as such, x^2+4x+4<0 when x<-2. As x=-2 is a root of the function, x^2+4x+4<=0 when x<=-2 is also true.
We’ve answered 319,200 questions. We can answer yours, too.Ask a question